KOLABORASI PENDIDIKAN DAN HUKUM SEBAGAI INSTRUMEN PENGUATAN CIVIC LITERACY DI ERA MODERNITAS - Umaidi Umaidi; Ely Ezir Marpaung (Universitas HKBP Nommensen, 2026)
Global transformation in the modern era, marked by digitalization, intensified relations between states, and the strengthening of transnational legal norms, presents new challenges to the quality of citizen participation and the resilience of democracy. In the context of increasingly globally connected nation-states, low civic literacy not only impacts weak domestic legal awareness but also contributes to citizens' inability to understand the dynamics of global governance and the principles of the rule of law across borders. To date, strengthening civic literacy has tended to be positioned sectorally within the realm of formal education without systemic integration with law as a normative framework and regulatory instrument of the state. This study aims to analyze a collaborative model between education and law as an instrument for strengthening civic literacy in the context of global modernity. The study uses a qualitative approach with a conceptual-analytical study design based on a systematic literature review of approximately 60 national and international scientific sources published between 2010 and 2025. The analysis is conducted using content analysis techniques and an interdisciplinary thematic synthesis of civic education theory and legal theory. The study's limitations lie in its conceptual approach without empirical field testing and its focus on the context of developing democracies. The research results show that collaboration between education and law creates a synergy between the educational function (internalization of values) and the regulatory function (enforcement of norms), which simultaneously strengthens legal culture and democratic participation. The formulated model encompasses three main pillars: (1) curriculum integration based on global legal literacy, (2) institutional partnerships between educational institutions and legal institutions, and (3) adaptive public policies to digital challenges and the globalization of norms. Practically, these findings contribute to the design of educational policies and legal reforms based on cross-sector collaboration, while also enriching the theoretical discourse on the integration of education and law in strengthening substantive democracy.